THE EFFECT OF INFORMATION ASYMMETRY ON EARNINGS QUALITY TO EARNINGS MANAGEMENT AS AN INTERVENING VARIABLE - AZHAR, SYAHRUL (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this research was to investigate the relationship between information asymmetry measured by bid-ask spread, and earnings quality measured by earning response coefficient. This relationship are mediating by earnings management which measured by discretionary accruals. The samples used in this research were 46 of the manufactures companies listed on Indonesia Stock Exchange 2009-2012 period. The result proved that information asymmetry was not predictor to earnings quality. In conclusion, earnings management become intervening variable between information asymmetry and earnings quality.   Keywords : information asymmetry, earnings quality, earnings management, intervening.